RESPONSIBILITIES AND PROFESSIONAL IMPORTANCE OF PHYSICAL EDUCATION IN PUBLIC HEALTH (Fiep Bulletin - online, 2017)
The insertion of the Physical Education Professional into healthcare is a recent and very important battle for the life qualityof the general population. The research objective was to raise references that show the importance and responsibilities that thePhysical Education professional takes concerning public healthcare. Therefore, literature research was conducted so as to endorseour research and we realized that with the admission of Physical Education professionals in the National Health System through SCFH(Support Center for Family Health) it is possible to check the benefits this professional can bring to the population. Furthermore, it isimportant that physical activity guided by a skilled professional has the most suitable effects for the person who practices it, as there isan entire control over the variables of training. In SCFH, each professional must be committed to their work according to their specificarea and, within it, the Physical Education professionals should work in order to develop the full individual, having the main objective ofpromoting health among the population. Also, the work of this professional within healthcare should be aimed at the physical, mentaland social well-being, achieving the proper balance between all these variables. Starting from the importance the physical educationprofessional takes on public healthcare, particularly in stimulating new lifestyle in people, it is suggested new research highlighting onthis matter and supporting new ideas related to health promotion.